Fight against human trafficking in Poland: from theory to practice - Banach-Gutierrez, Joanna Beata (New forms of human trafficking, 2024)
Human trafficking is one of the most dangerous phenomena arising in our world. This crime should be taken very seriously because the so-called vulnerable victims are people - women, girls, and children. However, in many recently reported cases the victims are men, searching for work abroad. In all these cases, the fundamental rights of individuals such as life, health, dignity and freedom are seriously endangered by traffickers. Human trafficking is often referred to as modern slavery. The reasons of human trafficking find their roots usually in poverty, lack of education and employment, homelessness, attitudes and norms towards sexuality or gender relations, socio-economical and judicial circumstances. Poland is a country of origin, a transit country, and a destination country for trafficked victims. This chapter will illustrate the essence of human trafficking, as a serious crime, the adopted legal regulations against it, and some data on the convictions. The findings of the research may indicate that the dominating forms of abuse in human trafficking are sexual exploitation and forced labor. Most of the identified victims in Poland are citizens of Poland, Ukraine, Romania, and Bulgaria. Poles also become victims abroad, mainly in the United Kingdom, the Netherlands, and Germany.